Artificial intelligence technologies in Chinese media content production - Ren, Yi (Journal of the Belarusian State University. Journalism, 2025)
It is noted that artificial intelligence technologies are currently being intensively used in the global media industry, leading to changes. Based on the analysis of scientific articles by media researchers and examples of media practices in Chinese media, the article proposes a timeline for the use of artificial intelligence in journalism, examines the models of artificial intelligence used in the production of media content, and highlights the positive changes caused by the introduction of automated technologies in the creation of content for Chinese traditional media and content for their social networks.